2016
DOI: 10.1097/sap.0000000000000640
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Optimal Individualized Surgical Management of Craniofacial Fibrous Dysplasia

Abstract: Based on clinical experience and surgical outcomes presented in this study, the surgical approach of craniofacial fibrous dysplasia should be tailored to individual patient's needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…The degree of craniofacial symmetry improvement was considered satisfactory (eight patients -57.14%) or partially satisfactory (six cases -42.86%) and the overall mean of the surgical results classified according to the need for new surgeries was 1.5±0.52, between categories I and II ( Figures 3 and 4 and Table 3). In this series, there was no poor, unsatisfactory result, category III and/ or category IV according to the previously published scales [23][24][25] .…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The degree of craniofacial symmetry improvement was considered satisfactory (eight patients -57.14%) or partially satisfactory (six cases -42.86%) and the overall mean of the surgical results classified according to the need for new surgeries was 1.5±0.52, between categories I and II ( Figures 3 and 4 and Table 3). In this series, there was no poor, unsatisfactory result, category III and/ or category IV according to the previously published scales [23][24][25] .…”
Section: Resultssupporting
confidence: 63%
“…For this, we used craniofacial photographs took by a professional photographer in a professional studio with three flashes. We classified preoperative and postoperative (12 months) photographs of all patients according to three previously published scales [23][24][25] : 1) Craniofacial aesthetics: excellent, good, regular or poor 23 . 2) Degree of improvement of craniofacial symmetry 24 : satisfactory result, craniofacial symmetry; partially satisfactoryresult, global improvement of craniofacial symmetry, however craniofacial asymmetry can still be detected; or unsatisfactory result, absence of noticeable improvement of the craniofacial symmetry after the surgical interventions.…”
Section: Evaluation Of Surgical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, decision for surgical approach should be based on age, affected craniofacial bone site, extension of anatomical zone, functional and/or aesthetic issue, preferences of patient, and surgical team experience. Denadai et al [ 8 ] suggested radical resection and immediate reconstruction for zone I, II, and IV in adult patient, while conservative shaving for younger age (<7 years) without visual impairment. Because of potential risk of recurrence or malignant change, authors also prefer radical resection when possible in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…In active ONJ, treatments can range from debridement of the necrotic bone to aggressive resection of the affected area [38]. Post-operative regrowth is common following conservative debulking and recontouring surgeries in craniofacial FD; therefore, if ONJ is treated surgically, the FD bone should be monitored to assess response to surgery [40]. As more FD/MAS patients are treated with bisphosphonates and anti-osteoclastic drugs, it is important to investigate ONJ and other long-term effects of these drugs in order to develop appropriate treatment and monitoring guidelines.…”
Section: Discussionmentioning
confidence: 99%